THE EFFECT OF APPLYING PQRST METHOD ON STUDENTS’ READING COMPREHENSION - Herbiana Sipayung and Lince Sihombing (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study deals with the effect of applying PQRST method on students’ reading comprehension. The objective of this study is to find out whether PQRST method significantly effect on students’ reading comprehension or not. This study was conducted by using experimental research design. The population of the study was the students of grade X of SMA Negeri 1 Sidamanik. There were sixty students as the sample of the research. This study conducted with two randomized groups namely experimental and control group. The experimental group was taught by using PQRST method while control group was taught using traditional method. The data of the study were obtain from students’ score of test. To determine the reliability of the test, the writer used the Kuder Richardson formula (KR-21). The result of the study showed that reliability of the test was 0.618. The data were analyzed by using t-test formula, the analysis showed that score students in the experimental group was significantly higher than that of students in the level of control group at the level of significance 0.05 with the degree of freedom (df) 58 the t-observed is 5.333 while t-table is 2.000. It can be concluded that applying PQRST method significantly affects on students’ reading comprehension. It means that the hypothesis is accepted.